Perkembangan Aktivitas Industri dan Bangkitan Aktivitasnya di Kecamatan Tegowanu, Kabupaten Grobogan - Danik Nur Puspita Sari; Fadjar Hari Mardiansjah (Jurusan Perencanaan Wilayah dan Kota, 2023)
Urbanization process has also shifted urban activities from urban cores its peripheries. Industrial development peripheries become one of the activities that strengthened rural-urban linkages in the form of core-peripheries interactions. This phenomenon also occurs in Semarang Metropolitan area, small towns in its peripheries as the locations for industrial development, including in Tegowanu District, Grobogan Regency. The development of industrial activities in the area also leads to other activities generation. The results show that industrial development in Tegowanu District appeared since 2009 by the development of a garment factory, which is followed by other industries, located in Mangunsari and Gebangan Villages. The industrial development is in a rural village area and industrial development in Tegowanu District is 23.08% per year. However, the generation of other activities in Mangunsari Villages is still low, although most of industrial activities’ development are located there. Tegowanu Kulon as an old urban village is the place where the most of other activities’ generated take place because industrial activities in Tegowanu District are still relatively new and developing, soo the impacts in generating other urban activities is still limited. However, the development of industrial activities in the area has resulted in more varied livelihoods and employment opportunities